Financial and economic determinants of firm default - Giulio Bottazzi; Marco Grazzi; Angelo Secchi; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2009)
This paper investigates the relevance of financial and economic variables as determinants of firm defaults. Our analysis is not limited to publicly traded companies but extends to a large sample of limited liability firms. We consider size, growth, profitability and productivity together with a standard set of financial indicators. Non parametric tests allow to assess to what extent defaulting firms differ from the non-defaulting group. Bootstrap probit regressions confirm that economic variables play both a long and short term effect. Our findings are robust with respect to the inclusion of Distance to Default and risk ratings among the regressors.
Keywords: C14; C25; D20; G30; L11; 330; firm default; financial indicators; selection and growth dynamics; kernel densities; stochastic equality; bootstrap probit regressions; Distance to Default; Insolvenz; Unternehmenswachstum; Unternehmensfinanzierung; Bootstrap-Verfahren; Industrie; Italien